A multicenter survey of the accessibility of essential medicines for children in China - Dai, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2020)
Objective: To investigate the availability, prices and affordability of essential medicines in pediatric population across China, in the hope of improving rational use of medicines. Methods: A multicenter cross-sectional survey of medicine prices, availability and affordability was conducted in 17 provinces, municipalities and autonomous region across east, south-central part, west and north of China. Data on 42 medicines used in pediatric population, both original and generic, were collected in 55 public hospitals from May 26 to June 2, 2017. Availability was expressed as the percentage of hospitals with stock of the target medicine on the day of data collection,and median price ratio (MPR) was the ratio of price upon investigation to international reference. Based on national minimum daily wage, affordability represents the number of working days needed to earn the expense which covers a standard course using the target medicine. Statistical software SPSS 13.0 was applied for descriptive analysis of availability, MPR and affordability. Results: Mean Availability of original and generic medicine was 33% and 32%, with median MPR being 5.43 and 1.55. Among the 19 medicines with price information for both original and generic product, the median MPR was 7.73 and 2.04 respectively. Regarding the five medicines used to treat four common pediatric diseases (pneumonia,peptic ulcer, congenital hypothyroidism, refractory nephrotic syndrome), the affordability was 0.63 (0.16-6.17) d for generic medicine, and 1.03 (0.16-11.53) d for its original counterpart. Conclusions: The availability to both original and generic products of the 42 medicines used in pediatric population was low in China. The prices of generic medicines seem to be lower and affordability higher than those of original medicines. There is an urgent need to improve the availability and affordability of pediatric medicines